Enhanced electronic structure and electrochemical active area of ternary NiCoFe-LDH and Cu nanowire composites for superior energy storage - Eom, Subin; Jung, Moo Young; Park, Jihye; Son, Ji-Won; Ahn, JeongHyeon; Kim, Sung Won; Yun, Yong Ju; Jun, Yongseok (Elsevier BV, 2026)
Climate change urgently necessitates the development of sustainable energy solutions alongside efficient energy storage devices. Among these, supercapacitors have emerged as promising candidates due to their fast charge/discharge capabilities and exceptional long-term cycle stability. In this study, NiCoFe-layered double hydroxide (NiCoFe-LDH) was successfully synthesized via electrodeposition onto copper nanowires (Cu NWs), which were prepared through electrochemical anodization followed by thermal reduction. The optimal Fe ratio in NiCoFe-LDH@Cu NW was determined through various electrochemical tests, with the 3-NiCoFe-LDH@Cu NW (Ni:Co:Fe = 5:3:3) exhibiting superior electrochemical performance, achieving a capacity of 130.20 μAh cm−2 at a current density of 3.0 mA cm−2. To evaluate practical applicability, an asymmetric supercapacitor (ASC) was fabricated using 3-NiCoFe-LDH@Cu NW as the positive electrode and 1-MXene@CuO NW as the negative electrode. The ASC demonstrated excellent energy storage performance, delivering an energy density of 1.69 mWh cm−2 at a power density of 19.27 mW cm−2, outperforming recently reported devices. Furthermore, the ASC retained 80.7 % of its initial capacity after 8000 cycles at 10 mA cm−2, with a coulombic efficiency of 102.9 %, highlighting its remarkable stability and efficiency.